Accelerating the development of vaccine microarray patches for epidemic response and equitable immunization coverage requires investment in microarray patch manufacturing facilities. (4th March 2023) - Scarnà, Tiziana; Menozzi-Arnaud, Marion; Friede, Martin; DeMarco, Kerry; Plopper, George; Hamer, Melinda; Chakrabarti, Ajoy; Gilbert, Philippe Alexandre; Jarrahian, Courtney; Mistilis, Jessica; Hesselink, Renske; Gandrup-Marino, Kristoffer; et al.
ABSTRACT: Introduction: There is a need for investment in manufacturing for vaccine microarray patches (vMAPs) to accelerate vMAP development and access. vMAPs could transform vaccines deployment and reach to everyone, everywhere. Areas covered: We outline vMAPs' potential benefits for epidemic preparedness and for outreach in low- and lower-middle-income countries (LMICs), share lessons learned from pandemic response, and highlight that investment in manufacturing-at-risk could accelerate vMAP development. Expert opinion: Pilot manufacturing capabilities are needed to produce clinical trial material and enable emergency response. Funding vMAP manufacturing scale-up in parallel to clinical proof-of-concept studies could accelerate vMAP approval and availability. Incentives could mitigate the risks of establishing multi-vMAP manufacturing facilities early.